An audit of diabetes self-management education programs in South Africa - Loveness Dube; Stephan Van den Broucke; William Dhoore; Kerry Kalweit; Marie Housiaux (SAGE Publishing, 2015)
Background: Diabetes is a significant contributor to the burden of disease worldwide. Since its treatment requires extensive self-care, self-management education is widely recommended, particularly in resource limited settings. This study aimed to review the current state of policies and implementation of diabetes self-management education (DSME) in South Africa, with a specific focus on cultural appropriateness. Design and Methods: The audit involved a review of policy documents and semi-structured questionnaires with providers and experts in public and private health services. Forty-four respondents were interviewed. Documents were analysed with reference to the International Standards for Diabetes Education from the International Diabetes Federation. Data were entered and analysed in excel to give a description of the DSME programs and ad hoc interventions. Results: Three guidelines for Type 2 diabetes and two for chronic diseases were retrieved, but none were specifically dedicated to DSME. Five structured programs and 22 ad-hoc interventions were identified. DSME is mostly provided by doctors, nurses and dieticians and not consistently linked to other initiatives such as support groups. Health education materials are mainly in English with limited availability. Conclusions: DSME in South Africa is limited in scope, content and consistency, especially in the public services. A National curricula and materials for diabetes education need to be developed and adapted to the socio-economic context, culture and literacy levels of the target populations. It is recommended that DSME would be addressed in national policies and guidelines to guide the development and implementation of standardised programs.